As estações ferroviárias do Triângulo Mineiro e Alto Paranaíba e suas interfaces: história e conservação - Carili, Clayton França (2015)
The implementation of the railway in Triângulo Mineiro and Alto Paranaíba helped to develop the area and connexion with other states: São Paulo, Goiás and Mato Grosso. The railway used to transport people and goods throughout many train stations in urban and rural areas and some major railroad complexes. There were many factors that led to the decline and abandonment of these properties: governmental policies which were in favour of road transportation and automotive industry, the replacement of the steam locomotive for electric and electric-diesel locomotives, changing part of the railway plan, removal of railways and loss of function of the buildings, extinction of passenger trains, which led the stations to lose its main purpose: people transport. 53% of the stations built inside the study area were demolished and most of them are in rural areas. There are several situations: stations on a precarious conservation state, most of them in the city s rural area, stations being used in urban and rural areas with new uses, stations working with cargo and goods transportation. The stations in Triângulo Mineiro and Alto Paranaíba area in Minas Gerais are the object of this dissertation, wherein the main interest lies on the stations that are in operation, 21 buildings, seeking to verify their conservation state, their agents and role in preserving the train memory. Maps, charts and tables were made for this collection s understanding, having visited the stations that are listed by the cultural heritage and the ones that are in operation with new functions. Field records were made allowing the understanding of these properties in operation. It is observed that only the buildings listing, despite ensuring the non-demolition, does not help on the use and preservation of these stations, because there are some buildings that have this protection level, but are abandoned and in disrepair. The use of these stations by a train company, operating with cargo and goods transportation do not also guarantee the buildings preservation, as they are not treated with any preservation interest, their maintenance are precarious. The using by these companies are various, however, only a few stations have internal spaces dedicated to the railroad memory. Most of the stations did not have preservation projects with architects and specialists participation and the major concern, during maintenance process, is on the building s external part. The stations conservation begins on the local government interest, that preserve these properties, most of them are in urban areas, the major challenge is on their using definition and occupancy, especially in the countryside, wherein the buildings uses must be sustainable, as regards the appreciation and management of this heritage.